Modulation of TLR/NF-κB/NLRP Signaling by Bioactive Phytocompounds: A Promising Strategy to Augment Cancer Chemotherapy and Immunotherapy - Fakhri, Sajad; Moradi, Seyed Zachariah; Yarmohammadi, Akram; Narimani, Fatemeh; Wallace, Carly E.; Bishayee, Anupam (Frontiers in Oncology, 2022)
Background: Tumors often progress to a more aggressive phenotype to resist drugs. Multiple dysregulated pathways are behind this tumor behavior which is known as cancer chemoresistance. Thus, there is an emerging need to discover pivotal signaling pathways involved in the resistance to chemotherapeutic agents and cancer immunotherapy. Reports indicate the critical role of the toll-like receptor (TLR)/nuclear factor-B (NF-κB)/Nod-like receptor pyrin domain-containing (NLRP) pathway in cancer initiation, progression, and development. Therefore, targeting TLR/NF-κB/NLRP signaling is a promising strategy to augment cancer chemotherapy and immunotherapy and to combat chemoresistance. Considering the potential of phytochemicals in the regulation of multiple dysregulated pathways during cancer initiation, promotion and progression, such compounds could be suitable candidates against cancer chemoresistance. Objectives: This is the first comprehensive and systematic review regarding the role of phytochemicals in the mitigation of chemoresistance by regulating the TLR/NF-κB/NLRP signaling pathway in chemotherapy and immunotherapy. Methods: A comprehensive and systematic review was designed based on Web of Science, PubMed, Scopus, and Cochrane electronic databases. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were followed to include papers on TLR/NF-κB/NLRP and chemotherapy/immunotherapy/chemoresistance by phytochemicals. Results: Phytochemicals are promising multi-targeting candidates against the TLR/NF-κB/NLRP signaling pathway and interconnected mediators. Employing phenolic compounds, alkaloids, terpenoids, and sulfur compounds could be a promising strategy for managing cancer chemoresistance through the modulation of the TLR/NF-κB/NLRP signaling pathway. Novel delivery systems of phytochemicals in cancer chemotherapy/immunotherapy are also highlighted. Conclusion: Targeting TLR/NF-κB/NLRP signaling with bioactive phytocompounds reverses chemoresistance and improves the outcome for chemotherapy and immunotherapy in both preclinical and clinical stages.